Do people choose what makes them happy and how do they decide at all? A theoretical inquiry - Niklas Scheuer (ZBW - Leibniz Information Centre for Economics, 2020)
We develop a theoretical model that jointly explains optimal choices and happiness. We work with constant elasticity of substitution functions for utility and happiness. Employing a choice framework, individuals are confronted with two options. When there exists a trade-off, we determine parametric conditions for which individual happiness and utility coincide as well as oppose each other. Comparing the empirical evidence of Benjamin et al. (2012), our model can explain three out of four possible happiness-utility combinations. Regarding how individuals actually decide, our findings suggest that this is partly random. This explanation accounts for the remaining 11.2 % of individuals.
Keywords: D11; D91; I31; 330; Consumer Economics; Theory; General Welfare; Well-Being; Micro-Based Behavioral Economics